The oxygen stable isotope composition of CRM 125-A UO2 standard reference material. (November 2022) - Oerter, Erik J.; Singleton, Michael; Pili, Eric; Klosterman, Michael R.; Shemesh, Aldo; Agrinier, Pierre; Deinhart, Amanda; Yam, Ruth; Assulin, Maor; Elish, Eyal; McDonald, Luther; Tenner, Travis; et al.
Abstract: While there is a clear need for standardized reference materials for analytical calibrations and for inter-laboratory comparisons, there are not currently any for the oxygen stable isotopic composition of uranium oxides. In this paper we summarize the results from four laboratories by seven different methods of oxygen stable isotope analyses using fluorination techniques of CRM 125-A UO2 Standard Reference Material. We synthesize these data and methods to arrive at a consensus oxygen stable isotope composition for CRM 125-A δ 18 O = −9.63‰ (±0.29‰) VSMOW. We discuss methodological differences between analytical approaches, including furnace vs laser heating, fluorination using BrF5 or ClF3, as well as calibration strategies. We highlight the potential effects of calibration scale compression from single-point calibrations using reference material with δ 18 O values having a large relative difference from the sample being analyzed. We demonstrate how calibration scale compression can yield differences in calibrated δ 18 O values up to ∼2‰ for samples with ∼20‰ difference from a single reference material, if the calibration slope of different analytical systems differs by 0.1. We suggest the use of liquid water calibration standards sealed in silver capillary tubes for multi-point calibrations of fluorination analysis systems. Highlights: We collected δ 18 O values on CRM 125-A UO2 from four laboratories by seven methods. The consensus CRM 125-A δ 18 O value is -9.63‰ (± 0.29‰) VSMOW. We introduce use of liquid water standards for calibration in fluorination systems.